The Role of Interprofessional Communication in Enhancing the Quality of Hospital Health Services: A Scoping Review - Wahyuningsih, Aries; Firmanda, Giovanni Iga (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
Interprofessional communication is vital in delivering high-quality hospital healthcare services by promoting teamwork, minimizing errors, and enhancing patient outcomes. This study explores the role of interprofessional communication in improving the quality of hospital healthcare services. The research employed a scoping review design, utilizing data from Elsevier and ScienceDirect databases for articles published between 2017 and 2025. The review process adhered to PRISMA guidelines 2020, with inclusion criteria focusing on articles discussing interprofessional communication in hospital settings. A standardized data extraction form was used to record study characteristics, communication interventions, and outcomes. Thematic analysis was applied to map and synthesize key themes and subthemes. A rigorous selection process yielded 14 relevant articles, ensuring consistency and scientific credibility. The findings identified two main themes: strategies to enhance interprofessional communication—such as structured tools like SBAR and interdisciplinary meetings—and the impact of communication on healthcare quality, including improvements in patient safety, clinical outcomes, and team collaboration. Subthemes included communication barriers, leadership support, and continuous training. The study concludes that hospitals should prioritize implementing structured communication protocols and cultivating a culture of teamwork and ongoing professional development to optimize service delivery and patient safety.